PERAN SELF EFFICACY DALAM MENINGKATKAN WORK LIFE BALANCE, WORK ENGAGEMENT, TERHADAP KINERJA PEGAWAI - Affandi, Abdurachman; Sutianingsih, Sutianingsih (Universitas Boyolali, 2023)
This research aims to examine the influence of work-life balance, and work engagement, on employee performance with self-efficacy as a mediator variable. The subjects who participated in this research were 30 employees of Batik Putra Laweyan. Data was collected using a questionnaire and analyzed using multiple linear regression techniques. The results of the analysis show that work-life balance and work engagement influence self-efficacy. Work-life balance does not affect employee performance. Work engagement and self-efficacy influence employee performance. Self-efficacy mediates work-life balance, and work engagement on employee performance. Keywords: employee performance, self-efficacy, work engagement, work-life balance